The Analysis of Mathematical Communication's Ability in Derivative Materials Observed from Introvert and Extrovert Personality Types - Salisa Rojiatur Rohmah; Hanif Uli Rona (Hipotenusa : Journal of Mathematical Society, 2020)
The purpose of this study is to determine mathematical communication skills that assessed from introvert and extrovert personality types, to determine the strengths and weaknesses of each personality type. This research is a qualitative descriptive study. The class subjects are students of SMA Kartika III-1 Banyubiru, grade XI MIPA 2 (Mathematics and Natural Science). The subjects of the research are 2 introvert and 2 extrovert personality types' students. The procedures of collecting data are written tests, interviews, questionnaires and documentation. The results of this study show that mathematical communication skills in terms of introvert personality type are able to meet 1 indicator. That is the ability to explain ideas, situations and mathematical relations in writing. In contrast, the extrovert personality type meets 2 indicators of mathematical communication skills. There is the ability to express daily events in language or mathematical symbols and the ability to read mathematical symbols. The strengths of introvert personality type are able to explain ideas verbally and in writing. Then the weaknesses are difficult to understand the problem of mathematical images and symbols. In contrast to the introvert, extrovert personality's strengths are able to understand mathematical symbols, and then its weaknesses are hard to understand mathematics questions.